Chronic musculoskeletal pain in European older adults: Cross‐national and gender differences. (12th December 2017) - Cimas, M.; Ayala, A.; Sanz, B.; Agulló‐Tomás, M.S.; Escobar, A.; Forjaz, M.J.
Abstract: Background: In an ageing Europe, chronic pain is a major public health problem, but robust epidemiological data are scarce. This study aimed to analyse the prevalence of and factors associated with chronic musculoskeletal pain by gender in older adults of 14 European countries. Methods: A cross‐sectional study was performed from wave 5 of the Survey of Health, Ageing and Retirement in Europe (SHARE). The study included people ≥50 years residing in Austria, Belgium, Czech Republic, Denmark, Estonia, France, Germany, Italy, Luxembourg, the Netherlands, Slovenia, Spain, Sweden and Switzerland. Chronic pain was defined as being bothered by joint and/or back pain for the previous 6 months. Multivariable Poisson regression models with robust variance were performed to analyse prevalence ratio by covariates, stratified by sex. Results: A total of 61, 157 participants were included. Overall prevalence of chronic musculoskeletal pain was 35.7% (28.8–31.7), ranging from 18.6% (17.1–20.1) for Switzerland to 45.6% (43.3–47.8) for France. Prevalence was higher in women than in men: 41.3% (40.2–42.4) versus 29.1% (28.0–30.3). Chronic musculoskeletal pain was lower in men aged >75 years (PR = 0.82; 0.72–0.92) than the younger (50–59) group. Separated/divorced status presented opposite effects among men (PR = 0.85; 0.76–0.96) and women (PR = 1.12; 1.03–1.21) compared with married, and unemployment was a significant factor in men (PR = 1.21; 95% CI 1.02–1.43) compared with employed. Conclusions: Musculoskeletal pain in older European adults is very frequent, especially in women, with large differences depending on the country of residence. Health policy makers should prioritize strategies aimed at improving the prevention and management of chronic musculoskeletal pain in Europe. Significance: This study provides epidemiological data of chronic musculoskeletal pain in older adults. Reported differences contribute to highlight the relevance of considering a gender perspective in chronic musculoskeletal pain research. Cross‐national comparison also offers a map of differences that improves the knowledge of this chronic condition in Europe.